2014
DOI: 10.1017/jfm.2014.361
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a free-shear layer in the vicinity of a viscosity-stratified layer

Abstract: The stability of a mixing layer made up of two miscible fluids, with a viscosity-stratified layer between them, is studied. The two fluids are of the same density. It is shown that unlike other viscosity stratified shear flows, where species diffusivity is a dominant factor determining stability, species diffusivity variations over orders of magnitude do not change the answer to any noticeable degree in this case. Viscosity stratification, however, does matter, and can stabilize or destabilize the flow, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It has shown that two types of instability can commonly take place in these flows; the most frequently observed and investigated is Kelvin-Helmholtz instability which has significant role on mixing of the fluids [22]. This instability is well known for its overturning billowing patterns, cats-eye structure, and its ability to mix effectively [1,23]. The chance of Kelvin-Helmholtz instability occurring is when the stratification is weak and the thickness of density transition layer between two layers of different densities is comparable to the shear layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that two types of instability can commonly take place in these flows; the most frequently observed and investigated is Kelvin-Helmholtz instability which has significant role on mixing of the fluids [22]. This instability is well known for its overturning billowing patterns, cats-eye structure, and its ability to mix effectively [1,23]. The chance of Kelvin-Helmholtz instability occurring is when the stratification is weak and the thickness of density transition layer between two layers of different densities is comparable to the shear layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, figure 18 shows a time series of the concentration profile for a case with rad s, and mm. It is known that viscosity stratification in shear flows can lead to instability in certain regimes (Yih 1967; Sahu & Govindarajan 2014). However, the coupled viscosity distribution and velocity profile in the rheometer system are highly nonlinear, and the flow cannot be analysed in terms of simple viscosity-stratified layers of fluid.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that a similar analysis was performed by Sahu and Govindarajan [15], in which they have investigated the viscous instability of free shear layer in the vicinity of a viscous stratified mixed layer. Their results show that di↵usivity has no influence on the stability of this class of shear flows but viscosity stratification has a significant role on the stability characteristics.…”
mentioning
confidence: 84%
“…For a vertical wall (✓ = 90 ), in the absence of surface tension (S = 0), we have f = 0. It may be checked that 1 + B + C + D = 0, showing that c = 1 is a root of the cubic equation (15). The other two roots are those of the quadratic equation…”
Section: Vertical Wall No Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation